Distribution, prevalence and a new physiologic race of Puccinia graminis tritici in Brasil, in 1972 and 1973 - Coelho, Elisa Thomaz (Pesquisa Agropecuaria Brasileira, 2014)
The 15/65 race of Puccinia graminis tritici was predominant in the 255 stem rust samples collected in Brazilian wheat regions, in 1972 and 1973; that Taco accounted 74% and 50% respectively of the samples. The other races identified, in order of decreasing prevalence, were: in 1972: 11, 15/71, 17, 17/63, 17/61 and 17 T; in 1973,11/74,17/63,15/71,11 and 11 T. The 11/74 race was virulent only ongenos Sr 8 and Sr 11. It was first determined in 1973, second in order to prevalence, comprised about 35% of the samples. The combination of the genes Sr 7a and Sr 11 confers resistance to all occurrent races.